Ceramides and metabolic profiles of patients with acute coronary disease: a cross-sectional study - Zhang, Liang; Tan, Dawei; Zhang, Yang; Ding, Yaodong; Liang, Huiqing; Zhang, Gong; Xie, Zhijiang; Sun, Nian; Wang, Chunjing; Xiao, Bingxin; Zhang, Hanzhong; Li, Lin; et al. (Frontiers in Physiology, 2023)
Metabolic Syndrome (MS) is a rapidly growing medical problem worldwide and is characterized by a cluster of age-related metabolic risk factors. The presence of MS increases the likelihood of developing atherosclerosis and significantly raises the morbidity/mortality rate of acute coronary syndrome (ACS) patients. Early detection of MS is crucial, and biomarkers, particularly blood-based, play a vital role in this process. This cross-sectional study focused on the investigation of certain plasma ceramides (Cer14:0, Cer16:0, Cer18:0, Cer20:0, Cer22:0, and Cer24:1) as potential blood biomarkers for MS due to their previously documented dysregulated function in MS patients. A total of 695 ACS patients were enrolled, with 286 diagnosed with MS (ACS-MS) and 409 without MS (ACS-nonMS) serving as the control group. Plasma ceramide concentrations were measured by LC-MS/MS assay and analyzed through various statistical methods. The results revealed that Cer18:0, Cer20:0, Cer22:0, and Cer24:1 were significantly correlated with the presence of MS risk factors. Upon further examination, Cer18:0 emerged as a promising biomarker for early MS detection and risk stratification, as its plasma concentration showed a significant sensitivity to minor changes in MS risk status in participants. This cross-sectional observational study was a secondary analysis of a multicenter prospective observational cohort study (Chinese Clinical Trial Registry, https://www.who.int/clinical-trials-registry-platform/network/primary-registries/chinese-clinical-trial-registry-(chictr), ChiCTR-2200056697), conducted from April 2021 to August 2022.